Kepemimpinan Efesien Bagi Peningkatan Pelayanan Terhadap Remaja Usia 15-18 Tahun - Imurni Ndruru; Sandra Rosiana Tapilaha (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
Efficient Leadership for Adolescents Aged 15-18 Years, Which teenagers can help them develop responsibility, leadership skills, and social maturity which are very important for their development. Of course, effective leadership is not just taking control, but also leading with empathy, listening, and providing inspiration to their friends. This is a very important skill and will help them grow and develop in their current and future social environments. A youth leader must also set a good example to others. One of them is Effective Communication. Leaders must be able to understand and respect their peers, of course this really enables them to build good relationships and resolve conflicts. Teenagers who lead must encourage the group to work together. and Youth leaders must continually improve their leadership skills.